1996
DOI: 10.1183/09031936.96.09122671
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide in exhaled air

Abstract: Much interest is now being focused on measurements of nitric oxide (NO) in exhaled air. In healthy subjects exhaled NO seems to originate mainly in the nasal airways, whereas the contribution from the lower respiratory tract is low.In certain inflammatory airway disorders, the excretion of NO into the airways is altered resulting in changes in the levels of NO in exhaled air. New techniques have been developed to measure NO release at different levels of the airways: asthmatics show increased orally-exhaled NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
112
1
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(120 citation statements)
references
References 66 publications
5
112
1
2
Order By: Relevance
“…Standardization is necessary for the collection of acceptable and comparable data both within one center and between several centers. For eNOsb measurements, standardization primarily involves the expiratory target flow of 50 ml/s, as eNO is inversely related to flow (9)(10)(11)(12)(13). Furthermore, standardization requires the following criteria: inhalation to total lung capacity during the inspiratory maneuver, inspired NO concentration of <5 parts per billion (ppb), exhalation time of ≥4 s for children <12 y and ≥6 s if older, duration of expiratory plateau at target flow of ≥2 s, expiratory pressure level of 5-20 cm H 2 O for velum closure, calibration, hardware, and measurement techniques (9).…”
mentioning
confidence: 99%
“…Standardization is necessary for the collection of acceptable and comparable data both within one center and between several centers. For eNOsb measurements, standardization primarily involves the expiratory target flow of 50 ml/s, as eNO is inversely related to flow (9)(10)(11)(12)(13). Furthermore, standardization requires the following criteria: inhalation to total lung capacity during the inspiratory maneuver, inspired NO concentration of <5 parts per billion (ppb), exhalation time of ≥4 s for children <12 y and ≥6 s if older, duration of expiratory plateau at target flow of ≥2 s, expiratory pressure level of 5-20 cm H 2 O for velum closure, calibration, hardware, and measurement techniques (9).…”
mentioning
confidence: 99%
“…For this reason, it was recently suggested that the monitoring of lung function and symptoms are not sensitive enough to reflect the extent of airway inflammation [25]. The measurement of FE,NO has been proposed as a simple noninvasive means of monitoring the level of airway inflammation [11±13, 16,26]. It has also been demonstrated that FE,NO is increased after allergen-induced asthmatic reactions [27,28], whereas it is reduced after treatment with inhaled steroids [15] in a dose-related fashion [14].…”
Section: Discussionmentioning
confidence: 99%
“…This method has been shown to be successfully applicable in both adults and children. The FE,NO was measured at the plateau of the end-expiratory reading and expressed in parts per billion (ppb) according to guidelines [16]. The FE,NO considered in the data analysis were always measured at the plateau FE,NO, taking the plateau of the endexpiratory carbon dioxide reading as representative of an alveolar sample [13,17].…”
Section: Lung Function and Nitric Oxide Measurementmentioning
confidence: 99%
“…Of chemokines eotaxin, IL-8, regulated on activation, normal T-cell expressed and secreted (RANTES) and others are of interest, but with the exception of IL-8, for which good assays are available (35,36), the measurements of chemokines have limited clinical interest. Another inflammation marker, which is produced by many cells and is increasingly used as a tool to reflect inflammation in the airways is nitric oxide (NO) in exhaled air (37)(38)(39)(40). Its position in the clinical routine is still uncertain mostly because of methodological problems and difficulties in the interpretation of the results (40-42).…”
Section: Monitoring Of Inflammationmentioning
confidence: 99%